Pentingnya Vitamin D untuk Mencegah Beberapa Penyakit - Ramatillah, Diana Laila; Indrayani, Ni Putu Kristina; Sari, Novi Triana; Virginia, Vivi; Syelvia, Fauziah Debby; Furi, Mefina Ratna; Murti, Yuliza (BERDIKARI, 2025)
Vitamin D plays a crucial role in calcium and phosphorus metabolism, bone health, and immune system function. Deficiency of vitamin D in adolescents increases the risk of impaired bone growth and various chronic diseases. This community service activity aimed to enhance the understanding of 11th-grade students at SMK N 31 Jakarta regarding the importance of vitamin D in disease prevention. The method involved an interactive educational session using PowerPoint presentations, accompanied by pre-test and post-test assessments to evaluate knowledge improvement. The results showed an increase in the average post-test score to 88.07%, compared to 86.16% in the pre-test, indicating a positive improvement in students' understanding. The program effectively raised students’ awareness of the importance of vitamin D intake through sun exposure and a nutritious diet. It also demonstrated the effectiveness of interactive health education in increasing adolescents health knowledge.